DEVELOPMENT OF EDUCATIONAL COMIC MEDIA BASED ON POWERPOINT CLASS III INDONESIAN LANGUAGE CONTENT - Hermawanti, Oermila; Susilaningsih, Sri (Universitas Negeri Semarang, 2020)
This study was motivated by the results of Indonesian language lesson in some students who did not reach the Minimum Score Criteria because of limited teaching materials and learning media. This study was research and development (R&D). This study aimed to develop comic media on powerpoint, to assess the feasibility, and the effectiveness of the media on the theme earth and universe of Indonesian language. the data was collected by observasion, interviews, questionsnaires, tests, and documentation. The subject of this research was the three grade students of Karangayu 03 elementary school. The result showed that: (1) comic media on powerpoint successfully developed according to the needs of teachers and students; (2) comic media on powerpoint was very feasible to be used with the percentage of assessment from material experts amounting to 94% and from media experts at 88% .; (3) comic media on powerpoint was effective used Indonesian language learning as evidenced by an increase in the average student learning outcomes through the t test of 16,733 and the average incrase of 0.6 with medium criteria. In conclusion, the comic media on powerpoint was very feasible and effective for helping the students to learn about Indonesian language.